ASPEK SPIRITUAL DALAM NOVEL TUHAN IZINKAN AKU MENJADI PELACUR KARYA MUHIDIN M DAHLAN : Spiritual Aspects In The Lovely Of God Let Me Become A Property Of Muhidin M Dahlan - Karim, Asman Budiman, Muhammad Yusnan & Taufik (Uniqbu Journal of Social Sciences, 2020)
Literary work is a container of ideas, ideas, and an author about social phenomena that are captured and experienced by the author as outlined in the form of work. Research describes aspects of spirituality in God's Novel Let Me Become a Prostitute! the work of Muhidin M Dahlan. The method in this research is descriptive qualitative. Qualitative research is conducted by prioritizing the depth of appreciation of the interaction between concepts being studied empirically. The results showed that the spiritual aspects contained in the novel Lord Let Me Be a Prostitute! Is Aqeedah, sharia, and morals. Aqeedah consists of monotheism and faith in destiny. Sharia includes worship and siyasa while muamalah and munakahat are not found. As for the morals include the morals to God, the morals for both parents, and the morals in accepting Allah's provisions while the feeling of shame (Al-Haya) is not found. It also found a religious feeling that is more directed to its existence as a human being because it is personal in nature and its scope is broader than religion which is only limited to the teachings and links.